Hot Spots on Brake Disks – Model Reduction and Stability Discussion. Issue 1 (29th November 2013) - Graf, Matthias; Ostermeyer, Georg‐Peter
Abstract: Sliding friction results in heat generation. One design aim of brake systems is for the temperature field to rise homogeneously, but experiments have repeatedly shown a characteristic inhomogeneous temperature pattern on the disk, known as Hot Spots. This phenomenon is undesired, as it leads to noise, vibration, and material disruption. The uneven temperature distribution arises from what are known as "Thermoelastic Instabilities". The solutions for temperature and displacements must be obtained in four dimensions: three spatial dimensions and one time dimension. The industrial design process requires massive parameter studies and a fast solution of the model. To develop such models, strategies which avoid discretization come into the focus. The presented model is based on the application of global Ansatz functions for the fields, which are scaled to fulfil boundary conditions. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)